2020
DOI: 10.3390/pharmaceutics12050470
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Orodispersible Films of Isoniazid for Pediatric Tuberculosis Treatment

Abstract: Child-appropriate dosage forms are critical in promoting adherence and effective pharmacotherapy in pediatric patients, especially those undergoing long-term treatment in low-resource settings. The present study aimed to develop orodispersible films (ODFs) for isoniazid administration to children exposed to tuberculosis. The ODFs were produced from the aqueous solutions of natural and semi-synthetic polymer blends using electrospinning. The spinning solutions and the resulting fibers were physicochemically cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
0
38
0
1
Order By: Relevance
“…The fibers produced by 5% PCL solution are narrower than those produced by 10% PCL solution. It has been well reported that the nanofibers produced by electrospinning enlarge with the increase of polymer concentration used for synthesis [ 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibers produced by 5% PCL solution are narrower than those produced by 10% PCL solution. It has been well reported that the nanofibers produced by electrospinning enlarge with the increase of polymer concentration used for synthesis [ 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the thickness, hydrophobicity and molecular interaction of fibers and transporting molecules can be a tool to impact release, would the fiber diameter and pore size be another tool to manipulate the release? It has been well reported that the fiber diameter produced by electrospinning can be reduced by decreasing the polymer concentration used for synthesis process [ 11 , 12 , 13 ]. It was also reported in microfiltration that the flux of molecules can be altered by changing the microstructure of the nanofiber membranes such as the fiber diameter and porosity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it can be used in the case of swallowing problems, such as Parkinson’s disease, stroke, multiple sclerosis, esophagitis, and allergies [ 4 , 5 ]. In geriatrics and pediatrics, it can play a huge role due to its easy and unnoticed application, so patients prefer this dosage form to per os tablets [ 6 , 7 ]. It is a useful form of drug administration from the chemical perspective, because the API and gastric acid do not contact each other, so the stomach can be protected from the API and vice versa [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…El uso de nanofibras para el tratamiento de la TB u otras micobacteriosis es un campo fértil de investigación, se han incorporado fármacos como estreptomicina, isoniacida, pirazinamida y claritromicina con resultados variables (53) . Sin embargo, unas películas diseñadas para la administración oral de isoniacida demostraron una alta eficiencia de desintegración, liberación y encapsulamiento del fármaco (54) . La utilización de nanofibras también se ha propuesto en la innovación de las técnicas de diagnóstico de TB, por ejemplo, se han preparado nanofibras como biosensores electroquímicos para la detección de ADN de Mycobacterium tuberculosis, las nanofibras resultantes presentaron una alta sensibilidad de detección (55) .…”
Section: Nanofibrasunclassified